Long Noncoding RNA NTT Context-Dependently Regulates MYB by Interacting With Activated Complex in Hepatocellular Carcinoma Cells - Chang, Ya-Sian; Lee, Ya-Ting; Yen, Ju-Chen; Chang, Yuli C.; Lin, Li-Li; Chan, Wen-Ling; Chang, Wei-Chiao; Lin, Shyr-Yi; Chang, Jan-Gowth (Frontiers in Oncology, 2021)
Background: Long noncoding RNA (lncRNA) mediates the pathogenesis of various diseases, including cancer and cardiovascular, infectious, and metabolic diseases. This study examined the role of lncRNA NTT in the development and progression of cancer. Methods: The expression of NTT was determined using tissues containing cDNA from patients with liver, lung, kidney, oral, and colon cancers. The expression of cis-acting genes adjacent to the NTT locus (CTGF, STX7, MYB, BCLAF1, IFNGR1, TNFAIP3, and HIVEP2) was also assessed. We used knockdown and chromatin immunoprecipitation (ChIP) assays to identify the cis-acting genes that interact with NTT. Results: NTT was most significantly downregulated in hepatocellular carcinoma (HCC), while a higher NTT level correlated with a shorter survival time of patients with HCC. Multivariate analysis indicated NTT was not an independent predictor for overall survival. MYB was significantly upregulated, and its increased expression was associated with dismal survival in HCC patients, similar to the results for NTT. NTT knockdown significantly decreased cellular migration. ChIP of HCC cell lines revealed that NTT is regulated by the transcription factor ATF3 and binds to the MYB promoter via the activated complex. Additionally, when NTT was knocked down, the expression of MYB target genes such as Bcl-xL, cyclinD1, and VEGF was also downregulated. NTT could play a positive or negative regulator for MYB with a context-dependent manner in both HCC tissues and animal model. Conclusion: Our study suggests that NTT plays a key role in HCC progression via MYB-regulated target genes and may serve as a novel therapeutic target.